ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PROFITABILITAS PERUSAHAN-PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ 45 - admin, CHRISTINA GUNAWAN . B1112044 (Jurnal Manajemen Update, 2016)
The company's ability to generate profits is called profitability. Many factors can affect the profitability of the company. Some of them are Total Asset Turnover (TATO), Debt to Total Assets (DAR), company size, inflation and interest rates were examined in this study. The purpose of this study was to determine the effect of Total Asset Turnover (TATO), Debt to Total Assets (DAR), company size, inflation and interest rates on profitability either partially or simultaneously on a company that consistently indexed in LQ45. The method used in this study is based on a descriptive study with a quantitative approach. In this research, data processing, and hypothesis testing was performed using statistical tests such as the classical assumption test, multiple linear regression, t test and F. Based on the test results t is known that only TATO used in this study have a significant effect on profitability. Based on F test result that Total Asset Turnover (TATO), Debt to Total Assets (DAR), company size, inflation and interest rates simultaneously significant effect on profitability. Keywords: Total Asset Turnover (TATO), Debt to Total Assets (DAR), Company Size, Inflation, Interest Rate and Profitability.